PENGARUH KOMPENSASI FINANSIAL, MOTIVASI, DISIPLIN TERHADAP KINERJA KARYAWAN UD JOYO SEDULUR ASMOROBANGUN-KEDIRI - Hamdani, Iman (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to analyze whether there was a significant effect of the financial compensation, motivation, and discipline variables partially or simultaneously on the performance of UD Joyo Sedulur employees in Asmorobangun Village, Kediri. The approach used in this study is a quantitative approach and the type of descriptive research, with the sampling technique using non-probability sampling, the sample size used is 40 employees, and the data analysis technique uses descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, and hypothesis testing with SPSSv24 software. The results showed that there was a significant influence between the variables of financial compensation, motivation and discipline either partially or simultaneously on the performance of UD Joyo Sedulur employees in Asmorobangun Village-Kediri.